2021
DOI: 10.1093/mnras/stab2135
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the self-lensing population in optical surveys

Abstract: The vast majority of binaries containing a compact object and a regular star spend most of their time in a quiescent state where no strong interactions occur between components. Detection of these binaries is extremely challenging and only few candidates have been detected through optical spectroscopy. Self-lensing represents a new means of detecting compact objects in binaries, where gravitational lensing of the light from the visible component by the compact object produces periodic optical flares. Here we s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Several recent theoretical works have highlighted the feasibility of large surv e ys, including astrometric missions (Gould & Salim 2002 ;Barsto w et al 2014 ;Brei vik, Chatterjee & Larson 2017 ;Mashian & Loeb 2017 ;Yalinewich et al 2018 ;Andre ws, Brei vik & Chatterjee 2019 ;Chawla et al 2021 ) and microlensing searches (Masuda & Hotokezaka 2019 ;Wiktorowicz et al 2021 ), to unco v er large new populations of black holes in binary orbits. Massive spectroscopic surv e ys are also beginning to probe this territory through brute force blind searches for radial velocity variations characteristic of massive compact objects (Yi, Sun & Gu 2019 ;Wiktorowicz et al 2020 ;Price-Whelan et al 2020 ).…”
mentioning
confidence: 99%
“…Several recent theoretical works have highlighted the feasibility of large surv e ys, including astrometric missions (Gould & Salim 2002 ;Barsto w et al 2014 ;Brei vik, Chatterjee & Larson 2017 ;Mashian & Loeb 2017 ;Yalinewich et al 2018 ;Andre ws, Brei vik & Chatterjee 2019 ;Chawla et al 2021 ) and microlensing searches (Masuda & Hotokezaka 2019 ;Wiktorowicz et al 2021 ), to unco v er large new populations of black holes in binary orbits. Massive spectroscopic surv e ys are also beginning to probe this territory through brute force blind searches for radial velocity variations characteristic of massive compact objects (Yi, Sun & Gu 2019 ;Wiktorowicz et al 2020 ;Price-Whelan et al 2020 ).…”
mentioning
confidence: 99%
“…Recent population synthesis studies by Wiktorowicz et al (2021) have estimated the amount of self-lensing systems that will be observed by upcoming surveys such as LSST, TESS, and Zwicky Transient Facility to be of the order of 10 3 -10 4 . A large fraction of these systems will undergo self-lensing events that would result in amplifications smaller than a millimagnitude difference, thus, the pulses would be indistinguishable from noise.…”
Section: Discussionmentioning
confidence: 99%
“…A large fraction of these systems will undergo self-lensing events that would result in amplifications smaller than a millimagnitude difference, thus, the pulses would be indistinguishable from noise. However, Wiktorowicz et al (2021) estimate up to 200 of such systems that will create self-lensing pulses that will be detectable and distinguishable by the surveys. This would put the amount of discovered self-lensing systems on the same order as that of known X-ray binary (XRB) systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent theoretical works have highlighted the feasibility of large surveys, including astrometric missions (Gould & Salim 2002;Barstow et al 2014;Breivik et al 2017;Mashian & Loeb 2017;Yalinewich et al 2018;Andrews et al 2019;Chawla et al 2021) and microlensing searches (Masuda & Hotokezaka 2019;Wiktorowicz et al 2021), to uncover large new populations of black holes in binary orbits. Massive spectroscopic surveys are also beginning to probe this territory through brute force blind searches for radial velocity variations characteristic of massive compact objects (Yi et al 2019;Wiktorowicz et al 2020;Price-Whelan et al 2020).…”
Section: Introductionmentioning
confidence: 99%